The Effect of The Problem-Based Learning Model Assisted by Quizizz Paper Mode on Student Learning Outcomes in Science Subjects - Farhan, Zidan Ahmad; Nuraeni, Fitri; Alindra, Afridha Laily (MID Publisher International, 2024)
In the learning process, challenges arise when students lack concentration and motivation to absorb new knowledge, especially in science subjects, resulting in decreased learning outcomes. The low learning outcomes of elementary school students are the background to this research. The aim of this research is to determine the improvement in science learning outcomes of students who use the Problem Based Learning learning model with the help of Quizizz Paper Mode media as compared to those who learn with the conventional model in elementary schools and to find out the effect of the Problem Based Learning learning model assisted by Quizizz Paper Mode media on results. student learning in science subjects in elementary schools. The research method used in this research is quasi-experimental in the form of a nonequivalent control group design on the topic of discussing magnetic forces with a sample of 40 students. Data collection techniques in this research used tests and documentation. Based on data analysis, the n-gain score in the experimental class was 0.6673 and the control class was 0.5498, meaning that students who used the Problem Based Learning learning model with the help of Quizizz Paper Mode media were better than using the conventional model in elementary school. Meanwhile, the results of the linear regression test obtained an rSquare value of 0.508 while the coefficient of determination was 50.8%, meaning that there was an influence of the Problem Based Learning learning model with the help of Quizizz Paper Mode media on student learning outcomes in elementary school science subjects.